The role of social workers in preventing school dropout: an evidence-based review of interventions - Cădariu, Ioana-Eva; Rad, Dana (Technium Social Sciences Journal, 2025)
School dropout remains an important problem for school systems worldwide, with extensive individual, social, and economic consequences. The present evidence-based narrative review examines the role of the school social worker in preventing school dropout by merging intervention methods documented in the international and Romanian literature. Interventions that were valued were thematically structured along four areas: individual-level support (such as mentoring and counseling), family-based engagement (such as home visiting, parenting courses), community-based partnerships (such as interagency networks and outreach initiatives), and school-wide system changes (such as inclusive policy and early warning systems). Results indicate that dropout prevention requires successful early identification, relational trust, interdisciplinary collaboration, and institutional support. The school social worker is also found to be the key facilitator in the bridge between students’ needs and resources within the school, family, and community. The review is on salient factors enhancing intervention effectiveness as well as discusses issues to implementation, particularly within Romania’s education sector. Practice, policy making, and research suggestions are also considered.